Síntese de [2]rotaxanos: relação entre a estrutura de pirazóis ligados ao filamento linear e a formação da molécula entrelaçada - Zimmer, Geórgia Cristiane (2015)
This work reports the synthesis of new [2]rotaxanes, [2]-[1,2-bis(aminocarbonyl- (1'-(1',1'-dimethylethyl)-1H-pyrazol-3'-yl))-ethane]-rotaxa-1,7,14,20-tetraaza- 2,6,15,19-tetraoxo-3,5,912,16,18,22,25-tetrabenzocicloexacosano], by fivecomponent clipping reaction, derived from isomers 1,3- and 1,5-pyrazoles, such as bulky groups in the thread. Firstly, performed the synthesis of pyrazoles using the ketoesters ([EtO2CC(O)C=C(R)OMe, where R =Me, Pr, Ph, p-F-Ph, p- Cl-Ph e p-Br-Ph] with N-tert-butilhidrazine hydrochloride and pyridine as base, furnished a series of 1,3-pyrazoles ethyl 1-(1,1-dimethylethyl)-1H-pyrazol-3- carboxylate in 69-81% of yields. For 1,5-pyrazoles, ethyl 1-(1,1-dimethylethyl)- 1H-pyrazol-5-carboxylate were use the same reagents for the synthesis of 1,3- pyrazoles, but using KOH as base. The yields for these compounds were 78- 88%. Hydrolysis was performed at the ester grouping pyrazoles with NaOH for the two isomers series, forming products acids1,3-pyrazoles (75-92%) and 1,5- pyrazoles (92-98%). This step is necessary because they are very important to obtain new threads. For the synthesis of threads were used the acids pyrazoles (1,3- and 1,5-isomers), reacting it with triphenyl phosphite, pyridine and ethylene diamine, with yield of 69-95% and 70-90% respectively. Pyrazoles were used as bulky groups in the threads to determine the effect of the substituent pyrazole in the formation of the new [2]rotaxanes. The synthesis of [2]rotaxanes were carried out with the threads, isophthaloyl dichloride, pxylylene diamine and triethylamine. Only the 1,3-threads formed [2]rotaxanes (7-19%). To study the stability of molecular subcomponents was used high temperatures in DMSO in two periods of time. It was observed that the molecular subcomponents were stable, because not having a total breakdown of the structure. Also, the NMR experiments were carried out using T1 experiments for threads and [2]rotaxanes, noting that with the increase in structure, smaller T1 values were obtained.